Factors associated with patients' satisfaction in the health care system in North Macedonia - Vera Dimitrievska; Ana Tomovska Misoska (University American College Skopje, 2020)
This paper examines the factors and approaches in patients' satisfaction in the health care delivery system in N. Macedonia. The study aims to assess how key service quality dimensions relate to an important measure of performance in patient satisfaction and to find the elements that are valued by patients and the reasons behind patient satisfaction or dissatisfaction. The main tool used in this study was the instrument developed for measuring service quality named as SERVQUAL. The overall patient-satisfaction item was skewed towards low patient satisfaction in the health care system: 2.43 on a scale of 1-3. The strongest predictors were experienced healthcare professionals (β = -0.32), expected diagnosis (β =0.14) and modern equipment (β =-0.130). The regression model explained 62% of the variance in overall patient satisfaction. The findings of the study are of great importance for public hospital administrators in N. Macedonia with respect to the outpatient aspects of service quality. The results of the study will serve for the strategic use of hospital sectors as an initial strategy for marketing healthcare, and expanding patient satisfaction. Other studies found that satisfaction can be influenced by different variables.
Keywords: 330; patient satisfaction; factors; hospitals